Survival of selected bacteria of Arcobacter genus in disinfectants and possibility of acquired secondary resistance to disinfectants - Šilha, David; Šilhová, Lucie; Vytřasová, Jarmila; Brožková, Iveta; Pejchalová, Marcela (My University, 2016)
Bacteria of the genus Arcobacter are today feared pathogens and represent a true threat, particularly in the form of alimentary infections. This study presents information on the inhibitory concentrations of selected disinfectant agents frequently applied in the Czech Republic, and particularly in the food industry for sanitation. The results of the study indicate that total inactivation of tested arcobacters are mostly at concentration of 5.0-15.0% in case of Desprej-disinfectant, 10.0-15.0% in case of Incidur-disinfectant, respectively 1.0-15.0% Guaa Profi Pool-disinfectant. Nevertheless, it has been confirmed that there is a real risk for secondary resistance of arcobacters to emerge in relation to certain decontaminants. Through repeated passages of arcobacters in a medium with low concentration of the disinfectant, we increased their primary resistance to the Incidur disinfectant to 1.5-3.5x (depending on species or origin). In the case of Desprej, the primary resistance of arcobacters to the substance was increased to even 1.5-5x. The emergence of resistance to antimicrobial substances is a worldwide problem. Potential acquisition of resistance (secondary resistance) in case of Arcobacter spp. was confirmed in this study for the first time in the Czech Republic.
Přežívání vybraných bakterií rodu Arcobacter v desinfečních přípravcích a možnost vzniku sekundární rezistence k desinfekcím
Keywords: Arcobacter spp.; disinfectant; resistence; secondary resistence; inhibition; Arcobacter spp.; desinfekce; rezistence; sekundární rezistence; inhibice